Modification of Human-Biometeorologically Significant Radiant Flux Densities by Shading as Local Method to Mitigate Heat Stress in Summer within Urban Street Canyons. (26th June 2013) - Lee, Hyunjung; Holst, Jutta; Mayer, Helmut
Abstract : Increasing heat will be a significant problem for Central European cities in the future. Shading devices are discussed as a method to mitigate heat stress on citizens. To analyze the physical processes, which are characteristic of shading in terms of urban human-biometeorology, experimental investigations on the thermal effects of shading by a building and shading by tree canopies were conducted in Freiburg (Southwest Germany) during typical Central European summer weather. Urban human-biometeorology stands for the variables air temperatureT a, mean radiant temperatureT mrt, and physiologically equivalent temperature PET, that is the human-biometeorological concept to assess the thermal environment which was applied. The measuring setup consists of specific human-biometeorological stations, which enable the direct or indirect determination ofT a, T mrt, and PET. With respect to both shading devices, theT a reduction did not exceed 2°C, while PET as a measure for human heat stress was lowered by two thermal sensation steps according to the ASHRAE scale. AsT mrt has the role of a key variable for outdoor thermal comfort during Central European summer weather, all radiant flux densities relevant to the determination ofT mrt were directly measured and analyzed in detail. The results show the crucial significance of the horizontal radiant flux densities forT mrt and consequently PET.